Assessing the population density of the spotted paca, Cuniculus paca , (Rodentia: Cuniculidae) on an Atlantic Forest island, southeastern Brazil - Ferreguetti,Átilla C. (2018)
ABSTRACT The spotted paca, Cuniculus paca (Linnaeus, 1766), is a Neotropical, opportunistic, frugivorous caviomorph rodent, that inhabits primarily broadleaf forests. We aimed to provide the first estimates of density of C. paca for the Ilha Grande, an island located in the Atlantic Rain Forest biome of Brazil. Density and population size were estimated using the total number of individuals observed along each trail through the program DISTANCE 7. Our estimates of density and population size reinforces the importance of the Ilha Grande as an important reservoir of the species. Therefore, the results presented herein can be a starting point to support future action plans for the species, making predictions regarding the ecosystem and management and conservation of the spotted paca. Furthermore, the results can be used as a surrogate for other regions in which the species occurs.